Production and characterization of breadfruit flour (Artocarpus altilis): an alternative for the elaboration of flakes for children’s alimentation - Arteaga, Cristina; Arias-Gutiérrez, Ruth; Rodríguez, Adriana; Heredia-Aguirre, Susana; Gozalbo, Mónica; Blesa, Jesús; Alvarado-Barba, Renata Alejandra; Ríos-Romero, Cristina Gabriela; Villavicencio Barriga, Dayana; Vásquez, Jessenia; Egas, Karol; Quiroga-Torres, Elizabeth; et al. (Frontiers in Nutrition, 2026)
IntroductionBreadfruit (Artocarpus altilis) represents a promising tropical crop with high nutritional potential and application in functional food development. This study aimed to produce and characterize gluten-free breadfruit flour (BF) and evaluate its use at 20.7% substitution in corn-based extruded flakes.MethodsPhysiologically mature breadfruit was peeled, cored, cut into 20 × 20 × 10 mm pulp cubes, dipped in 0.1% (w/v) sodium bisulfite for 2 min, tray-dried at 70°C (air velocity 1.5 m s−1), and milled to < 212 μm.ResultsThe resulting flour exhibited a moisture content of 10.8%, protein 10.1%, fat 2.4%, fiber 4.06%, and total phenolics of 298.7 mg GAE/100 g, with a predominance of polyunsaturated fatty acids (52.8%) and 41.4 mg β-carotene/100 g. Heavy metals (Pb = 0.085 mg/kg, Cd = 0.012 mg/kg) and aflatoxins (< 0.5 μg/kg) were below national safety limits, confirming product safety.DiscussionThe optimized formulation (F3, 20.7% BF) was extruded under a temperature profile of 80/110/135°C and 200 rpm, producing flakes with favorable expansion (4.0 ± 0.1), hardness (14.7 ± 0.4 N), and high sensory acceptability (7.9 ± 0.33). All products complied with microbiological standards. The integration of BF improved the nutritional and functional value of the flakes, offering a sustainable and safe alternative ingredient for developing fortified breakfast cereals. These findings highlight breadfruit flour as a technologically feasible, nutrient-dense, and sustainable resource to enhance food diversification and support nutrition-sensitive strategies addressing malnutrition in Ecuador and other tropical regions.